SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN POSISI PEMAIN IDEAL DALAM TIM SEPAK BOLA DENGAN METODE ALGORITMA GENETIKA - Alprianta, Hizkia; Honggowibowo, Anton Setiawan; Indrianingsih, Yuliani (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2012)
So far, there are coaches who are less precise in determining the ideal position of the player as it only relies on instinct and the ego of the players so that there is still a coach who has not been able to objectively assess the players.By utilizing the method of Genetic Algorithm as Decision Support System (DSS) in the process of determining the ideal position of a player who uses several criteria (multicriteria) to choose a proper player. DSS is helping coach in making the right decisions and Genetic Algorithm is used as a model for multicriteria weighting in the selection process. This application was built with tools Borland Delphi (7.0) as the user interface design and media processing PostgreSQL as its database. Based on these results we can conclude that this application expected to assist the coaches in the decision making process and can change the appraisal of which are subjective to more objective, to determine the ideal position for a player, can determine the best position of each position of a number of players and the expected results of the Genetic Algorithm on the system constructed in accordance with the results of manual calculations.